ISOLASI BAKTERI PENGHASIL ENZIM PROTEASE BACILLUS MEGATERIUM IROD3 DARI ONCOM MERAH PASCA FERMENTASI 72 JAM - Dhea Ayu Lestari; Sakti Imam Muchlissin; Ana Hidayanti Mukaromah; Sri Darmawati; Stalis Norma Ethica (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Protease  enzyme  has  function  to  hydrolyze  peptide  bonds  in  proteins  into simpler molecules to digest by the body which important to food industry. One of effort to increase the production of protease enzymes is looking for new sources of protease particularly from bacterial groups. The purpose of this study was to obtain an isolate of protease-producing bacteria found on post- fermentation oncom 72 hours, and to identify the protease-producing bacteria based on the analysis of 16S rRNA gene. Isolation and purification process of bacterial colony was carried out on Nutrient Agar medium with spread technique, production test of protease enzyme was performed using Selective Skim Milk Agar. The process of Molecular identification process was carried out  through  analysis  of  16S  rRNA  gene  fragment  sequences  which  were amplified using Polymerase Chain Reaction (PCR) method, and continued by sequencing. The result of bacteria isolation was found one isolate which has proteolytic activity in Skim Milk Agar medium which has clear zone diameter of 78.00 mm. A similarity analysis based on the 16S rRNA gene sequence showed that IROD3 (Indonesian Red Oncom Day-3) has 99% similarity level with the 16S rRNA gene fragment of Bacillus megaterium strain CS17 (access code Genbank: MG430224.1). Keywords:  Molecular  identification,  proteolytic  bacteria,  16S  rRNA  gene, Bacillus megaterium